2017
DOI: 10.1111/jorc.12195
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and health‐related quality of life amongst patients who are starting dialysis treatment

Abstract: S U M M A R YBackground: Chronic kidney disease (CKD) has a severe impact on patients' health-related quality of life (HRQL). The start of renal replacement therapy (RRT) significantly influences psychological, physical and social aspects of life. Objectives: To analyse the HRQL and psychological status (anxiety and depression) at the start of RRT. Methods: We undertook an observational descriptive cross-sectional study. A total of 152 patients starting RRT were recruited for the study. HRQL was measured by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 38 publications
(42 reference statements)
2
35
0
5
Order By: Relevance
“…Peritoneal dialysis was associated with better scores than HD for both generic and kidney specific domains [84,85]. Nagaraja et al [44], on the other hand, reported that mean SF-6D utility scores among patients managed by PD were similar to those receiving HD (0.53 ± 0.10 vs 0.52 ± 0.11, respectively).…”
Section: The Kdqol-sf™ Toolmentioning
confidence: 98%
“…Peritoneal dialysis was associated with better scores than HD for both generic and kidney specific domains [84,85]. Nagaraja et al [44], on the other hand, reported that mean SF-6D utility scores among patients managed by PD were similar to those receiving HD (0.53 ± 0.10 vs 0.52 ± 0.11, respectively).…”
Section: The Kdqol-sf™ Toolmentioning
confidence: 98%
“…Сроки начала диализа в мировой практике крайне вариабельны, что связано с рядом факторов, которые могут играть роль при принятии решения [3]. С од-ной стороны, слишком раннее начало ГД, раньше реальной потребности в нем, является трудным и затратным как для самого пациента, так и для систе-мы здравоохранения в целом [10,11]. С другой сто-роны, слишком долгое откладывание начала диализа приводит к увеличению длительности воздействия уремической интоксикации на системы и органы па-циента с соответствующим нежелательным ростом рисков летальности и прогрессирования коморбид-ности.…”
Section: Discussionunclassified
“…Nowadays, several reversible MAOI are available in clinical practice for the treatment of neurodegenerative disorders and depression which renders them candidates for drug repurposing in pathologies associated with increased oxidative stress and cardiovascular mortality. Of note, these drugs are devoid of the irreversible MAOI sideeffects (in particular, the feared 'cheese effect') and might be used in patients with ESRD requiring hemodialysis where anxiety and depression are already present from the beginning of the therapy (Rebollo Rubio et al 2017).…”
Section: R a F Tmentioning
confidence: 99%